Pengaruh Kualitas Sumber Daya Manusia terhadap Pengelolaan Badan Usaha Milik Desa Salo Dua Kabupaten Enrekang - Zulfia Syam; Andi Uceng; Muhammad Ikbal; Sandi Lubis (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this study was to determine the extent to which the quality of human resources affects the management of BUMDes in Salo Dua Village, Enrekang Regency. This research involved 43 respondents who served as both the population and the sample because it used the saturated sample method. The research approach applied was descriptive quantitative. Data collection was conducted through observation, literature review, and questionnaire distribution. Data analysis was conducted by applying validity and reliability tests using IBM SPSS Statistics version 21.0 software. The findings of this study indicate that 61% of the human resource quality variable falls into the “not good” category, and 64% of the BUMDes management variable also falls into the “not good” category. Factors that influence the quality of human resources in BUMDes management include motivation (68%), work environment (62%), and social skills (58%). Overall, the quality of human resources and BUMDes management in Salo Dua Village were found to have a significant influence. The ANOVA analysis results in a calculated F value of 1284,138 with a significance of 0.000, which means that the influence of the independent variables is significant. The partial t test also shows that the calculated t value (35.329) exceeds the t table value (1.683), which indicates that the quality of human resources has a significant influence on the management of BUMDes in Salo Dua Village, Enrekang Regency.